Music Composition “Sekar Layu” | Komposisi Musik Inovatif “Sekar Layu” - I Ketut Agus Darmayasa; Kadek Suartaya (Pusat Penerbitan LPPMPP ISI Denpasar, 2021)
Local culture (Bali) has influenced the mindset, attitude, behavior in interacting with the surrounding environment. The attachment of the concepts of living in society in Bali has enveloped the whole, namely there is a feeling in doing it. Processed feelings of pleasure-sadness, joy and sorrow, of course, are owned by humans in general based on their respective experiences. The feeling that the author experiences in living the author's life has inspired the author to make an idea in an innovative music composition. As the author has explained, the journey of empirical love that the author has experienced has inspired, and motivated the writer's inner touch to create a series of tones that gave birth to innovative works. The essential content of the empiricism has ignited the fire of the writer's creativity, and subsequently distributed that fire with the frame of the title Sekar Layu. Sekar Layu for writers is a form of recreation room that is applied to an innovative musical composition. Borrowing a set of creation methodology knives that are deemed appropriate to explore the nature of Sekar Layu. The methods that the author applies include the stages of exploration, improvisation, and formation. The motif of the Sape instrument (Kalimantan musical instrument) and the leluangan motif which was poured into the Barungan Gamelan Semar Pagulingan Saih Pitu became the medium of expression in this work. All these frameworks of thought are merged into an integral part that cannot be separated from the work. Hopefully enlightenment (catharsis) will be fruitful for the writer and all the supporters involved in the creation of Sekar Layu's innovative music composition.